Analisis Segmentasi Pasar Produk Yamaha Mio dari Perusahaan Yamaha - Hermawan, Francisca (Universitas Muhammadiyah Yogyakarta, 2010)
Currently the Company Yamaha Motor vehicles are th manufacturer to create a special automatic motor cycle for woman. Yamaha Mio is a market leader for authomatic motor cycle product. Strategy used by Yamaha is market segmentation strategy, target market, and placement positions. This strategy is one weapom powerful enought to penetrate the field of competition.The research was conducted thought questionnaires to one hundred respondents. After the data obtained and processed by using Chi Square (kai square).